KARAKTERISTIK PAPAN PARTIKEL DARI BAMBU DENGAN PEREKAT GETAH DAMAR - Ika Amalia Kartika dan Dara Fegy Pratiwi (Department of Agroindustrial Technology, Bogor Agricultural University, 2018)
The fiber content of bamboo is very high (59.8%), thus it is potential to be the raw material for particle board manufacture. In this study, resin of damar was used as adhesive to substitute the synthetic adhesive such as urea and phenol formaldehide. The objective of this study were to characterize the particle board produced from bamboo with adhesive of damar resin, and to investigate the effect of pressing time and amount of resin added on physical and mechanical properties. This research was conducted on pressing temperatures of 130 and 150°C using randomized block design with two factors, i.e. pressing time (10 and 14 min) and amount of resin added (12, 14, 16%). The result of variance analysis showed that pressing time affected water adsorption of particleboard, while amount of resin added affected its thickness swelling. Both factors did not have the effect on density, moisture content, modulus of elasticity and rupture, and internal bonding of particleboard. Process condition of 14% resin added, 10 min pressing time and 150oC pressing temperature produced the particleboard with best characteristics, i.e. density of 0.55 g/cm3, moisture content of 9.99%, water adsorption of 72.6% at 2 hand 83.5% at 24 h, thickness swelling of 10.5% at 2 hand 18.0% at 24 h,, MOE of 393.5 kgf/cm2, MOR of 51.7 kgf/cm2and IB 0.90 of kgf/cm2. These characteristics did not meet the standard of JIS A 5908-2003 and SNI 03-2105-2006.Keywords: adhesive, bamboo, damar, resin, particle board